Aplikasi Permintaan Barang Berbasis Java dan Mysql di PT. Kino Indonesia, TBK Sukabumi - Wawang Adi Darma (JURNAL BUANA INFORMATIKA CBI, 2019)
A Cosmetic Industry "PT. Kino Indonesia, Tbk "located on Jl. Raya Babakan Km. 12 Cikembar Sukabumi Regency is a companyengaged in the Cosmetic Industry. Product data processing system for factory purposes at PT. KINO INDONESIA, TBK hasused Excel Application systems as its data processing system. So the company PT. Kino Indonesia, Tbk requires a form of computer application that can be run quickly, efficiently and precisely in its use such as a more practical Goods RequestApplication. Applications that are specifically designed to be able to melt requests for goods by the User and can be accessed by the Admin without having to re-login to update the data to be pulled, there is no need to re-record the different reports to make a stock inventory report, helping to avoid the difference in the final report. The display form that will be used has several main menus such as Data menu, Transaction menu and Report menu. Java and MySql programs are used by authors to buildthis system.